Oxidative Stress and Cytoskeletal Reorganization in Hypertensive Erythrocytes - Ivette Martínez-Vieyra; Isaac Hernández-Rojo; Víctor Hugo Rosales-García; Aracely Evangelina Chávez-Piña; Doris Cerecedo (Antioxidants)
Oxidative stress is widely recognized as a key mechanism in the development of hypertension. Under pathological conditions, such as in hypertension, oxidative stress leads to irreversible posttranslational modifications of proteins, which result in loss of protein function and cellular damage. We have previously documented physiological and morphological changes across various blood and bone marrow cell lineages, all of which exhibit elevated oxidative stress. While cytoskeletal changes in erythrocytes have been well characterized in hereditary diseases, this is the first study, to our knowledge, to investigate cytoskeletal reorganization in erythrocytes from hypertensive patients. To this end, we compared the expression patterns and subcellular distribution of key cytoskeletal proteins in erythrocytes from hypertensive individuals with those from normotensive subjects using Western blot, flow cytometry, and confocal microscopy. Our results revealed the presence of three erythrocyte subpopulations with differential expression of glycophorin A. The persistent oxidative environment in hypertensive patients causes dysregulation in the expression of glycophorin A, Band 3 protein, protein 4.1, and ankyrin, as well as the reorganization of spectrin. These alterations in protein expression and distribution suggest that oxidative stress in hypertensive individuals may induce structural modifications, ultimately impairing erythrocyte membrane elasticity and function.